2022
DOI: 10.3390/jcm11185403
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endoscopic Submucosal Dissection and Radical Surgery for Early Gastric Cancer in Remnant Stomach

Abstract: (1) Background: Endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) in the remnant stomach or gastric tube is not yet widespread and few studies have compared the short-term and long-term outcomes with radical surgery. (2) Methods: A total of 73 consecutive patients with EGC in the remnant stomach or gastric tube who underwent ESD or radical surgery between October 2009 and October 2020 were retrospectively analyzed in this study. Baseline characteristics, post-operative complications, qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Other studies have also demonstrated that gastric cancer in the gastric tube following esophagectomy is occasionally found, with an incidence of 1.0–7.0% and a 10-year cumulative incidence rate of gastric tube carcinoma (GTC) of 5.7% [ 8 , 9 ]. We have identified several factors contributing to the increased morbidity of this pathology.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies have also demonstrated that gastric cancer in the gastric tube following esophagectomy is occasionally found, with an incidence of 1.0–7.0% and a 10-year cumulative incidence rate of gastric tube carcinoma (GTC) of 5.7% [ 8 , 9 ]. We have identified several factors contributing to the increased morbidity of this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Although gastric cancer in the remnant stomach or gastric tube is typically detected at an advanced stage and surgical resection of the total remnant stomach has been the standard treatment for a long time, radical resection of advanced disease is technically demanding and carries high surgical morbidity rates [ 5 , 8 , 9 , 12 ]. Currently, the detection of early gastric cancer (EGC) in the remnant stomach or gastric tube is increasing due to follow-up endoscopic surveillance programs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations